Systemic Antibiotics and Chlorhexidine Associated with Periodontal Therapy: Microbiological Effect on Intraoral Surfaces and Saliva - Mendes, Stella de Noronha Campos; Esteves, Camila Machado; Mendes, Juliana Alethusa Velloso; Feres, Magda; Figueiredo, Nathalia; de Miranda, Tamires Szeremeske; Shibli, Jamil Awad; Figueiredo, Luciene Cristina (Antibiotics (Basel), 2023)
The effect of systemic antibiotics on the microbial profile of extracrevicular sites after periodontal treatment is currently the subject of research. This study evaluated the microbiological effects on different oral cavity sites of scaling and root planing (SRP) combined with antimicrobial chemical control in the treatment of periodontitis. Sixty subjects were randomly assigned to receive SRP alone or combined with metronidazole (MTZ) + amoxicillin (AMX) for 14 days, with or without chlorhexidine mouth rinse (CHX) for 60 days. Microbiological samples were evaluated by checkerboard DNA–DNA hybridization until 180 days post therapy. The adjunctive use of antibiotics plus CHX significantly reduced the mean proportions of red complex species from subgingival biofilm and saliva (p < 0.05). Furthermore, the analysis of all intraoral niches showed a significantly lower mean proportion of the red complex species in the same group. In conclusion, the concomitant use of antimicrobial chemical control (systemic and local) demonstrated a beneficial effect on the composition of the oral microbiota.